2022
DOI: 10.15252/embj.2021110145
|View full text |Cite
|
Sign up to set email alerts
|

K27‐linked ubiquitylation promotes p97 substrate processing and is essential for cell proliferation

Abstract: Conjugation of ubiquitin (Ub) to numerous substrate proteins regulates virtually all cellular processes. Eight distinct ubiquitin polymer linkages specifying different functional outcomes are generated in cells. However, the roles of some atypical polyubiquitin topologies, in particular linkages via lysine 27 (K27), remain poorly understood due to a lack of tools for their specific detection and manipulation. Here, we adapted a cell-based ubiquitin replacement strategy to enable selective and conditional abrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Similar to Gp78 (Morito et al, 2008), HERC3 may function as an E4 enzyme that elongates the Ub chains initiated by RNF5/185, as it directly binds to Ub (Cruz et al, 2001). Alternatively, HERC3 may modify the Ub chains initiated by RNF5/185 by adding non-canonical Ub chains, such as K27 chains, which promote the p97-proteasome pathway (Shearer et al, 2022), as HERC3 has been shown to promote K27-linked polyubiquitination (Zhang et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Gp78 (Morito et al, 2008), HERC3 may function as an E4 enzyme that elongates the Ub chains initiated by RNF5/185, as it directly binds to Ub (Cruz et al, 2001). Alternatively, HERC3 may modify the Ub chains initiated by RNF5/185 by adding non-canonical Ub chains, such as K27 chains, which promote the p97-proteasome pathway (Shearer et al, 2022), as HERC3 has been shown to promote K27-linked polyubiquitination (Zhang et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…K27-, K29- and K33-poly-ubiquitin chain types are associated with proteasomal degradation of several proteins. For instance, like K48-chains, K27-chains are important facilitators of substrate processing by proteasomes [39]. K27- and K29-chains destabilise several key innate immune proteins, including NLRP3 [40], MDA5 and RIGI [41, 42], ULK1 [43], STING [44], IRF3 and IRF7 [45], among others [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Non-proteolytic roles for polyubiquitination include, for K6 linkages, mitochondrial homeostasis ( Durcan et al, 2014 ) and the DNA damage response ( Wu-Baer et al, 2003 ; Elia et al, 2015 ; Blount et al, 2020 ), and for K27 linkages, cellular proliferation ( Shearer et al, 2022 ) and the innate immune response ( Yin et al, 2019 ). K29 polyubiquitin linkages play a role in the cellular stress response and in regulating the cell cycle ( Yu et al, 2021 ) while K33-linked chains are involved in T cell activation and signaling ( Huang et al, 2010 ; Yang et al, 2015 ).…”
Section: The Ubiquitin-proteasome Systemmentioning
confidence: 99%